Effect of Foliar Application of Organic And Inorganic Nutrient Solutions on Growth And Yield Of Maize (Zea Mays L.) (Journal of Pharmaceutical Negative Results, 2022)
The field experiment was carried out a farmer’s field in Sitheri village, Attur Taluk, Salem District, Tamil Nadu, India during kharif season of 2018 in order to evaluate the effect of foliar application of organic and inorganic nutrient solutions on growth, yield, nutrient uptake and economics of maize. The field is laid out with seven treatment and replicated thrice. The treatment consists of control water spray, polyfeed 1 %, DAP 2 %, humic acid 40 ppm, seaweed 10 %, panchagavya 3 %, vermiwash 2 % on 20 and 45 DAS. Among the different foliar application of organic and inorganic nutrients solutions tried out, foliar application of polyfeed @ 1% resulted in higher plant height on 30, 60 DAS and harvest (56.38, 143.50, 160.25 cm), dry matter production at harvest (12024 kg ha1), number of grains cob-1 (360), grain yield (4824 kg ha-1) and stover yield (7132 kg ha-1). The least parameters was observed in control treatment with plant height on 30, 60 DAS and harvest (35.71, 109.17, 125.85 cm), dry matter production (10730 kg ha-1), number of grains cob-1 (310), grain yield (3852 kg ha-1) and stover yield (6365 kg ha-1).